Analysis Of Land Cover Change And Its Impacts On Soil Quality And Water Availability - Ruth Riah Ate Tarigan (CERED Indonesia Institute, 2025)
Land cover change is one of the major drivers of environmental degradation, significantly affecting soil quality and water availability, particularly in rapidly developing regions. This study aims to analyze land cover changes and assess their impacts on soil quality and water availability over a multi-year period. The research employed a quantitative approach using remote sensing and Geographic Information System (GIS) techniques. Multi-temporal satellite imagery was used to identify land cover changes, while soil quality indicators and hydrological parameters were analyzed to evaluate environmental impacts. The results indicate a substantial conversion of vegetated areas into agricultural land and built-up areas, leading to increased soil degradation, reduced soil organic matter, and declining water availability. Areas experiencing intensive land cover change showed higher vulnerability to erosion and reduced water infiltration capacity. These findings highlight the critical role of sustainable land management and spatial planning in mitigating the negative impacts of land cover change. The study provides valuable insights for policymakers and environmental managers in developing effective strategies to preserve soil quality and ensure sustainable water resources.